Report 12: Training Programs for Maximum Manpower Effectiveness, Proceedings of a Conference, February 1952 - Chartier, Roger (Relations industrielles / Industrial Relations, 1953)
The article briefly reviews "Report 12: Training Programs for Maximum Manpower Effectiveness, Proceedings of a Conference, February 1952," (57 pages).